The role of exopolymers in bacterial adhesion - Azeredo, Joana (1999)
The importance of exopolymers in cell adhesion to a hydrophilic surface was established by studying the adhesion of three mutants of Sphingomonas paucimobilis, high, medium and low polysaccharide producers, to non coated and coated glass with the respective exopolymer. TR and CV were found to produce exopolymers with surfactant properties. These surfactants can easily coat the glass surface, making glass hydrophobic and thus enhancing adhesion. It was hypothesised that the exopolymers bound to the glass surface trough their hydrophilic parts and the exopolymers present at the surface of bacteria can bind together, overcoming the energy barrier created by the negative charge of both surfaces.